Supply or Demand, that is the Question: Decomposing Euro Area Inflation - Paolo Pasimeni (Intereconomics, 2022)
This paper studies the recent trends in inflation in the euro area and estimates to what extent the current inflationary pressures are driven by demand expansion and by supply side disruptions. First of all, consumer price inflation is particularly pronounced in goods and less so in the case of services. Energy and food are the most relevant components of rising consumer prices, accounting for almost three-quarters of total headline inflation. The fact that price pressure comes mainly from sectors with a high import content suggests that disruptions along international supply chains may play a key role. The paper then focuses on producer prices at the sectoral level and presents a methodology to decompose the rise in inflation between supply and demand impulses. It finds that, in the present context, supply factors are the main driver and account for at least 80% of the current increase in producer prices in industry and in each one of the manufacturing sectors with the highest price pressures. There are nevertheless some differences across countries. These findings imply that, if repairing supply-side problems and disruptions along supply chains is the priority, then promoting the right investment may be more urgent than cooling demand down. Country heterogeneity in the relative importance of demand and supply factors, then, may lead to different degrees of effectiveness of monetary policy and to a risk of divergences.
Keywords: C83; E31; E37; L6; 330